Antioxidant Activity and Kinetic Characterization of Chlorella vulgaris Growth under Flask-Level Photoheterotrophic Growth Conditions - Jesús Alberto Coronado-Reyes; Evelyn Acosta-Ramírez; Miranda Valeria Martínez-Olguín; Juan Carlos González-Hernández (Molecules, 2022)
C. vulgaris is a unicellular microalgae, whose growth depends on the conditions in which it is found, synthesizing primary and secondary metabolites in different proportions. Therefore, we analyzed and established conditions in which it was possible to increase the yields of metabolites obtained at the flask level, which could then be scaled to the photobioreactor level. As a methodology, a screening design was applied, which evaluated three factors: type of substrate (sodium acetate or glycerol); substrate concentration; and exposure-time to red light (photoperiod: 16:8 and 8:16 light/darkness). The response variables were: cell division; biomass; substrate consumption; and antioxidant activity in intracellular metabolites (ABTS•+ and DPPH•). As a result, the sodium acetate condition of 0.001 g/L, in a photoperiod of 16 h of light, presented a doubling time (Td = 4.84 h) and a higher rate of division (σ = 0.20 h−1), having a final biomass concentration of 2.075 g/L. In addition, a higher concentration of metabolites with antioxidant activity was found in the sodium acetate (0.629 Trolox equivalents mg/L ABTS•+ and 0.630 Trolox equivalents mg/L DPPH•). For the glycerol, after the same photoperiod (16 h of light and 8 h of darkness), the doubling time (Td) was 4.63 h, with a maximum division rate of σ = 0.18 h−1 and with a biomass concentration at the end of the kinetics of 1.4 g/L. Sodium acetate under long photoperiods, therefore, is ideal for the growth of C. vulgaris, which can then be scaled to the photobioreactor level.